Could Official Climate Denial Revive the Common Law as a Regulatory Backstop? - Mark P. Nevitt; Robert V. Percival (Washington University Law Review, 2018)
The Trump Administration is rapidly turning the clock back on climate policy and environmental regulation. Despite overwhelming, peer-reviewed scientific evidence, administration officials eager to promote greater use of fossil fuels are disregarding climate science. This Article argues that this massive and historic deregulation may spawn yet another wave of legal innovation as litigants, including states and their political subdivisions, return to the common law to protect the health of the planet. Prior to the emergence of the major federal environmental laws in the 1970s, the common law of nuisance gave rise to the earliest environmental decisions in U.S. history. In some of these cases, the Supreme Court issued injunctions to control significant sources of air and water pollution, but the Court later held that the Clean Water Act and Clean Air Act displaced the federal common law of nuisance. This Article argues that official climate denial may yet revive the common law as a regulatory backstop. If the U.S. Environmental Protection Agency reverses its earlier endangerment finding for greenhouse gas emissions, the Clean Air Act may no longer displace the federal common law of nuisance. While expert administrative agencies normally are more competent than the judiciary in fashioning regulatory policy, agencies that deny climate science should expect to face judicial intervention. As described in this Article, such action is consistent with the historic role the judiciary has played when other branches of government failed to prevent significant environmental harm.
Keywords: climate change; environmental law; environmental regulation; regulatory backstop; environmental protection agency; EPA; common law; tort law; nuisance; Clean Water Act; CWA; climate denial; federal common law; interstate nuisance; climate litigation; pollution; emissions; greenhouse gas; parens patriae; CAFE standards; Clean Air Act; CAA